Alternative integration strategies for simultaneous energy recovery and separation of oil sands pyrolysis products. (1st August 2019) - Zhang, Zisheng; Liu, Kailong; Li, Hong; Li, Xingang; Gao, Xin
Highlight: An integrated process is proposed to recover products and energy of oil sands products. The economic cost and environmental impact of integrated process is evaluated. Significant decrease of wastewater emissions was achieved for the integrated process. An increasing of energy recovery efficiency was achieved for the integrated process. Abstract: Pyrolysis process, as an important recovery technology of the heavy fossil resources, is limited to further utilization due to high energy consuming and wastewater emission especially for oil sands utility. This paper conducts an integrated process followed by the oil sands pyrolysis with an initial fractionation column of oil sands pyrolysis products based on the pyrolysis stream energy recovery unit. Three processes of separation of oil sands pyrolysis products based on integrated process and traditional ammonia spray process are proposed and compared through separation capability, economic functions, energy recovery efficiency and CO2 emissions analysis. Compared with traditional process, significant decline of 56.22% and 48.20% in total annual cost can be obtained by the effective integration of separation technology without wastewater emission. The energy recovery efficiency is raised from 8.65% to 74.23% and the CO2 emissions are eliminated. Furthermore, based on the using of novel integration technology, the cost will be decreased from 5.5 /t to 3.61 /t in the oil sands refining process consist of the pyrolysis, quenching and separation processes, including capital and operation cost.